Alternative Fiscal Rules for Norway - Leigh, Daniel (IMF Working Papers; Working Paper ;, 2007)
This paper considers long-term fiscal policy options in Norway, the world's fifth largest oil exporter, in light of the substantial expected increase in pension outlays. It compares the current fiscal rule, which targets a (central government structural) non-oil deficit equal to 4 percent of Government Pension Fund assets, with three alternatives that save a larger share of oil revenue and accumulate more assets to pay for aging costs. It also analyzes the macroeconomic consequences of accumulating more assets, finding that the additional income generated from more assets allows lower tax rates, with positive effects on long-term output.